Hepatic Choline Transport Is Inhibited During Fatty Acid–Induced Lipotoxicity and Obesity - Conor O’Dwyer; Rebecca Yaworski; Sakie Katsumura; Peyman Ghorbani; Kaelan Gobeil Odai; Julia R.C. Nunes; Nicholas D. LeBlond; Sabrin Sanjana; Tyler T.K. Smith; Shauna Han; Kaitlyn D. Margison; Tommy Alain; et al. (Hepatology Communications, 2020)
Choline is an essential nutrient and a critical component of the membrane phospholipid phosphatidylcholine (PC), the neurotransmitter acetylcholine, while also contributing to the methylation pathway. In the liver specifically, PC is the major membrane constituent and can be synthesized by the cytidine diphosphate–choline or the phosphatidylethanolamine N‐methyltransferase pathway. With the continuing global rise in the rates of obesity and nonalcoholic fatty liver disease, we sought to explore how excess fatty acids on primary hepatocytes and diet‐induced obesity affect choline uptake and metabolism. Our results demonstrate that hepatocytes chronically treated with palmitate, but not oleate or a mixture, had decreased choline uptake, which was associated with lower choline incorporation into PC and lower expression of choline transport proteins. Interestingly, a reduction in the rate of degradation spared PC levels in response to palmitate when compared with control. The effects of palmitate treatment were independent of endoplasmic reticulum stress, which counterintuitively augmented choline transport and transporter expression. In a model of obesity‐induced hepatic steatosis, male mice fed a 60% high‐fat diet for 10 weeks had significantly diminished hepatic choline uptake compared with lean mice fed a control diet. Although the transcript and protein expression of various choline metabolic enzymes fluctuated slightly, we observed reduced protein expression of choline transporter‐like 1 (CTL1) in the liver of mice fed a high‐fat diet. Polysome profile analyses revealed that in livers of obese mice, the CTL1 transcript, despite being more abundant, was translated to a lesser extent compared with lean controls. Finally, human liver cells demonstrated a similar response to palmitate treatment. Conclusion: Our results suggest that the altered fatty acid milieu seen in obesity‐induced fatty liver disease progression may adversely affect choline metabolism, potentially through CTL1, but that compensatory mechanisms work to maintain phospholipid homeostasis.